Islet Harvest in Carbon Monoxide-Saturated Medium for Chronic Pancreatitis Patients Undergoing Islet Autotransplantation. Issue 1 (December 2019) - Wang, Hongjun; Gou, Wenyu; Strange, Charlie; Wang, Jingjing; Nietert, Paul J.; Cloud, Colleen; Owzarski, Stefanie; Shuford, Betsy; Duke, Tara; Luttrell, Louis; Lesher, Aaron; Papas, Klearchos K.; et al.
Stresses encountered during human islet isolation lead to unavoidable β-cell death after transplantation. This reduces the chance of insulin independence in chronic pancreatitis patients undergoing total pancreatectomy and islet autotransplantation. We tested whether harvesting islets in carbon monoxide-saturated solutions is safe and can enhance islet survival and insulin independence after total pancreatectomy and islet autotransplantation. Chronic pancreatitis patients who consented to the study were randomized into carbon monoxide (islets harvested in a carbon monoxide-saturated medium) or control (islets harvested in a normal medium) groups. Islet yield, viability, oxygen consumption rate, β-cell death (measured by unmethylated insulin DNA), and serum cytokine levels were measured during the peri-transplantation period. Adverse events, metabolic phenotypes, and islet function were measured prior and at 6 months post-transplantation. No adverse events directly related to the infusion of carbon monoxide islets were observed. Carbon monoxide islets showed significantly higher viability before transplantation. Subjects receiving carbon monoxide islets had less β-cell death, decreased CCL23, and increased CXCL12 levels at 1 or 3 days post transplantation compared with controls. Three in 10 (30%) of the carbon monoxide subjects and none of the control subjects were insulin independent. This pilot trial showed for the first time that harvesting human islets in carbon monoxide-saturated solutions is safe for total pancreatectomy and islet autotransplantation patients.